Uncertainty-Aware Decision Making in Power Systems Including Energy Storage, Dynamic Line Rating and Responsive Demand as Multiple Flexibility Resources - Erdinc, F. Gulsen; Cicek, Alper; Erdinc, Ozan; Yumurtaci, Recep (IEEE, 2021)
The power systems structure has gradually evolved to a highly complex one especially with the introduction of greater amounts of non-dispatchable renewable systems and different new generation electric loads in the last decades. Therefore, in order to manage this complex structure with seminal resources of uncertainty, it is vital to utilize different types of flexibility options together in power system operation. Among them, employing the responsiveness of the demand side as well as different scales of energy storage options and dynamic line rating (DLR) possibility are generally considered as the pivotal approaches. Accordingly, an uncertainty-aware decision-making approach as mixed-integer linear programming model for power system operation considering the availability of responsive demand, pumped-hydro energy storage systems (PHESSs), as well as DLR possibility is proposed in this study. The consideration of all these flexibility options simultaneously in the context of such a decision-making approach poses the contribution of the proposed study over the existing literature. To test the effectiveness of the proposed model, four different case studies are conducted using IEEE 6 bus test system. In the results, it is seen that each flexibility tool has a significant effect on the operation of the power system economically and technically.
Keywords: Demand response; dynamic line rating; energy storage systems; uncertainty-aware decision-making; WIND POWER; Computer Science; Energy & Fuels; Engineering